Orbital infantile haemangioma: radiological features and treatment – case series and literature review. (2nd January 2019) - Albanese, Giorgio; Mohandas, Padma; Wells, Louise; Ravenscroft, Jane; Srinivasan, Jothsana; Thomas, Shery; Taylor, Timothy; Tambe, Katya
ABSTRACT: Aim: The aim of this study is to report a retrospective case series on orbital infantile haemangiomas (OIH). Radiological features and treatment with oral propranolol (OP) are illustrated along with an updated literature review.Methods: A retrospective chart review of six children, diagnosed with OIH from November 2015 to October 2016, was carried out. Only children with deep documented orbital involvement were included. All patients underwent magnetic resonance imaging (MRI) under general anaesthesia. OP was administered to the infants according to the Nottingham Children's Hospital guideline. As per the guideline, a preliminary paediatric assessment was performed and a 1 mg/kg test dose was administered, followed by definitive treatment at a dosage of 2 mg/kg in three divided doses.Results: Average age at presentation was within the first 3 weeks of life. T1 hypointensity, T2 hyperintensity, avid enhancement with contrast, and the presence of flow-voids appear a fixed pattern of OIH on MRI. Response to treatment was noticed within 4 weeks in all children, and two of them (33.3%) responded within the first 7 days. In two children (33.3%), the haemangioma became clinically undetectable by the seventh month of treatment, while the other four (66.6%) experienced an almost complete regression of the OIH by the last follow-up. No complications were found.Conclusions: Our series strengthens the understanding that MRI is the preferred imaging modality in the investigation of OIH, showing vascular features, detailed orbital extension, and possible associated malformations. OP is the treatment of choice for OIH, and our study confirms its safety and effectiveness.